2005
DOI: 10.1111/j.1399-5618.2005.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlates of current level of functioning in primary care‐treated bipolar patients

Abstract: Functioning in primary care-treated bipolar patients in maintenance phase of treatment is decreased not only due to specific disorder-related variables, but also due to frequent comorbidity with other psychiatric and medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 29 publications
(24 reference statements)
1
39
1
2
Order By: Relevance
“…Particularly, we found that bipolar patients with long duration of illness reported lower employment qualification and occupational status. This finding is congruent with previous studies reporting that the number of episodes had a negative impact on social functioning (Tohen et al 1990, Goldberg et al 1995, MacQueen et al 2000, Hajek et al 2005. It is possible that the high number of episodes may determine brain long-lasting biochemical changes that could have some consequences on global functioning in bipolar patients (Young et al 1993, Post 1993.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Particularly, we found that bipolar patients with long duration of illness reported lower employment qualification and occupational status. This finding is congruent with previous studies reporting that the number of episodes had a negative impact on social functioning (Tohen et al 1990, Goldberg et al 1995, MacQueen et al 2000, Hajek et al 2005. It is possible that the high number of episodes may determine brain long-lasting biochemical changes that could have some consequences on global functioning in bipolar patients (Young et al 1993, Post 1993.…”
Section: Discussionsupporting
confidence: 82%
“…Data from 1450 patients showed that 30-60% of bipolar patients had detectable levels of psychosocial impairment (MacQueen et al 2001). Long duration illness has been associated with impaired social functioning (Hajek et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In general, RCBD has been associated with worse disease outcome 9,10 and more severe disability. 7,11,12 More specifically, many factors have been described to be associated with RC, such as female gender, 5,13 earlier age at onset, 6,12 increased risk for suicide, 13,14 predominance of depression, 15,16 hypothyroidism, 6,17 bipolar type II disorder, 8,18,19 and higher rates of antidepressants use. 7,20 However, some of these associations are still controversial, and many studies have been criticized regarding aspects such as lack of a uniform definition of RC and use of heterogeneous samples.…”
Section: Introductionmentioning
confidence: 99%
“…Medical risk factors and GMC affect the course and the severity of BD as well as its treatment 2,16,17 , and their impact is significant due to reasons including quality of life, delivery of psychiatry and medical services, mortality 10 and disability 18 .…”
Section: Introductionmentioning
confidence: 99%